(untitled) (Annals of Bangladesh Agriculture, 2023)
The use of banana leaf ash extract (BLAE) as a replacement of Kosaric medium (KM) to grow spirulina (Spirulina platensis) was investigated. KM was partially replaced with more affordable and locally available BLAE at 0, 10, 30, 50, and 70% concentrations. The spirulina was grown for 18 days at room temperature in the experimental media with artificial lighting and aeration. By replacing KM with BLAE, the 30% replacement produced the highest biomass of S. platensis. It was observed that replacing of KM by 30% with BLAE produced biomass of 1.22 g/L, which was similar to that of 1.33 g/L with control (P <0.05). However, replacing more than 50% KM by BLAE failed to promote growth relative to the control. Moreover, chlorophyll a concentrations in the control were found comparable in up to 30% of BLAE concentrations. Protein, lipid, and fiber contents of S. platensis were found to be 57.67 ± 0.58, 11.59 ± 0.28, and 7.35 ± 0.37%, respectively, in 30% replacement of KM, compared to corresponding values of 58.02 ± 1.16, 12.25 ± 0.39, and 7.53 ± 0.32%, respectively, in control KM. At the 50% KM replacement level, these values dropped to 52.65 ± 0.98, 9.97 ± 0.51, and 7.25 ± 0.29%, respectively. In conclusion, cultivation of S. platensis with BLAE up to 30% replacement of KM may be viable without undue effect on the plant’s growth, pigmentation, or biochemical makeup. Ann. Bangladesh Agric. (2022) 26 (2) : 83-96